Research of the Test and Diagnosis of Torsional Vibration of RV Reducer - Huang Dishan; Liu Jinlei; Gu Jingjun (Jixie chuandong)
The torsional vibration testing and diagnostic technique for a RV reducer used in industrial robots under the condition of load inertia moment is described. Based on signal analysis of torsional vibration from the RV reducer,combining with the dynamics characteristics,the reason of abnormal torsional vibration of RV reducer is identified,and monitor of the dynamic performance of the RV reducer in the assembling process is realized. The research experiment shows that the technology will effectively monitor and diagnose the manufacturing defect of the RV reducer and help us to improve the products quality in the manufacturing process.